Metformin in patients with ischemic heart disease and type 2 diabetes mellitus: mechanism of action and clinical efficiency - Ekaterina Nikodimovna Kravchuk; M M Galagudza (Сахарный диабет)
Diabetes mellitus is one of the leading causes of death in modern society, primarily due to its cardiovascular complications. This factor drives search for novel pharmacologic agents to affect not only glycemic levels, but also the cardiovascular prognosis in diabetic patients with ischemic heart disease. Recent studies demonstrate that aside from basic blood glucose lowering action, metformin shows beneficial influence on blood rheology and vascular tone, hemostasis, oxidative stress, lipid spectrum and delivers and an ant-ischemic effect. Here we review clinical and experimental evidence on cardio- and vasoprotective effects of metformin, highlighting their molecular mechanisms.